Extreme ocean acidification reduces the susceptibility of eastern oyster shells to a polydorid parasite. Issue 11 (21st April 2017) - Clements, J C; Bourque, D; McLaughlin, J; Stephenson, M; Comeau, L A
Abstract: Ocean acidification poses a threat to marine organisms. While the physiological and behavioural effects of ocean acidification have received much attention, the effects of acidification on the susceptibility of farmed shellfish to parasitic infections are poorly understood. Here we describe the effects of moderate (pH 7.5) and extreme (pH 7.0) ocean acidification on the susceptibility of Crassostrea virginica shells to infection by a parasitic polydorid, Polydora websteri . Under laboratory conditions, shells were exposed to three pH treatments (7.0, 7.5 and 8.0) for 3‐ and 5‐week periods. Treated shells were subsequently transferred to an oyster aquaculture site (which had recently reported an outbreak of P. websteri ) for 50 days to test for effects of pH and exposure time on P. websteri recruitment to oyster shells. Results indicated that pH and exposure time did not affect the length, width or weight of the shells. Interestingly, P. websteri counts were significantly lower under extreme (pH 7.0; 50% reduction), but not moderate (pH 7.5; 20% reduction) acidification levels; exposure time had no effect. This study suggests that extreme levels – but not current and projected near‐future levels – of acidification (∆pH 1 unit) can reduce the susceptibility of eastern oyster shells to P. websteri infections.